Cordycepin Inhibits Triple-Negative Breast Cancer Cell Migration and Invasion by Regulating EMT-TFs SLUG, TWIST1, SNAIL1, and ZEB1 - Wei, Chunli; Khan, Md. Asaduzzaman; Du, Jiaman; Cheng, Jingliang; Tania, Mousumi; Leung, Elaine Lai-Han; Fu, Junjiang (Frontiers in Oncology, 2022)
Cancer metastasis is the most important cause of cancer-related death, and epithelial to mesenchymal transition (EMT) plays crucial roles in cancer metastasis. Cordycepin (CD) is highly enriched in the medicinally used Cordyceps mushroom. In this study, we conducted the antimetastatic activities of CD, specifically focusing on its regulatory effects on EMT-inducing transcription factors (EMT-TFs) in triple-negative breast cancer (TNBC). Our study showed CD to inhibit growth, migration and invasion of BT549 and 4T1 cancer cell lines, by employing cell viability assay and real-time cell analyses. The protein levels of N-Cadherin and E-Cadherin, as well as their transcription factors TWIST1, SLUG, SNAIL1 and ZEB1 in BT549 and 4T1 cells, were estimated by western blot assays. Results from dual-luciferase reporter assays demonstrated that CD is capable of inactivating EMT signaling pathway by inhibiting TWIST1, SLUG expression. Furthermore, in vivo studies with mice carrying cancer cell-derived allograft tumors showed the inhibitory effect of CD on cancer cell growth and metastasis. Furthermore, the additive/synergistic anti-metastasis effect of CD and thymoquinone (TQ), another natural product with promising anti-cancer roles, was demonstrated by combinational treatment. The results from this research indicate CD would be a promising therapeutic molecule against TNBC by targeting EMT-TFs, possibly in SLUG, TWIST1, SNAIL1 and ZEB1.